STUDY OF SEA LEVEL RISE USING SATELLITE ALTIMETRY DATA IN THE SEA OF DUMAI, RIAU, INDONESIA - Dewi Ariana; Cecep Kusmana; Yudi Setiawan (Department of Urban and Regional Planning, Diponegoro University, 2017)
Climate change and global warming has impacted the entire world. It has caused ice melting at the poles, climate extreme event, land subsidence which further affected sea level to rise, such as particularly, in Dumai coastal areas. To date, sea level rise is one of the important global issues. This increases the vulnerability effect in coastal areas which threatens human life, especially those living in coastal regions. Sea level rise can be forecasted by satellite imagery like ENVISAT, Topex/Poseidon, Jason-1 and Jason-2. This paper presents an approach to quantify the sea-level variations and sea level trend based on a combination of multi-mission satellite altimetry data over a period of 21 years (1993-2014). Monitoring of sea level rise was conducted by taking data from 6 stations. SLA was calculated using a typical moving average to reduce fluctuation. Sea level rise was calculated using a linear regression. Positive sea-level linear trends for the analysis period were estimated for sea level rise. The results showed that the range sea level rise reaching 4.80 mm/year to 5.61 mm/year has occured in Dumai. Dumai is predicted to have an additional sea level of 0.17-0.20 m by the year 2050, 0.41-0.48 m by the year 2100 and 0.65-0.76 m by the year 2150. The sea level rise trends in the North West part Dumai were higher than the other stations and down to South East. Based on the predicted results, Dumai should prepare plans to mitigate the rising of sea levels.